Auditions and … more auditions. Issue 2 (3rd July 2019) - Matthews, John; De Guevara, Victor Ladrón
ABSTRACT: This is the third of a four-part series of interrelated articles discussing the pedagogical, ideological, and sociological functions of the audition process in drama school training. For this third paper, we have re-interviewed our contributors in 2019, as they come towards the end of their formal training. We have asked them to compare their experiences of professional auditions with their experiences of auditioning for drama school recounted for the first two papers. Their accounts describe a complex and contradictory response to the process of audition which negates any possible interpretation of a linear or progressive development. This is apparently at odds with the pedagogic strategies pursued during their studies. Aiming to explain that dissonance we draw on the Bergsonian concepts of "clock time" and "psychological time" to help to classify and analyse these experiences, broadly categorizing these with reference to an actor's own conscious states in audition. Using Stanislavksi's writing as a key point of reference allows us to align our theorization with his discussion of a long-term and indeterminant pedagogical process of actor development. This is also counterpointed by Stanislavski's recognition that technique, no matter how it has been acquired or how competently it may have been mastered may not be sufficient for the actor to exercise her craft. In the last section of this article, we utilize Csikszentmihalyi theorization of "flow" states in order to reinforce the distinction felt by our interviewees between auditions determined by/in "clock time" and those inscribed within/by the psychological time, which Bergson calls la durée.